2016
DOI: 10.1177/1071100716681605
|View full text |Cite
|
Sign up to set email alerts
|

3D Model Analysis of Ankle Flexion on Anatomic Reduction of a Syndesmotic Injury

Abstract: Ankle position at the time of syndesmotic fixation did not affect overall ankle ROM when using a suture-button construct; however, overcompression was observed in all positions. The clinical impact of syndesmotic overcompression remains largely unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…It was clearly stated in the discussion on limitations that future studies are needed to investigate the quantitative and qualitative effects of ankle dorsiflexion on Achilles tendon tension and resultant syndesmotic reduction. There is conflicting literature, and conflicting opinion about the appropriate flexion angle for syndesmosis fixation, as summarized nicely in an article by Schon et al 3 We completely agree with the statement that it would be very interesting to determine what effect ankle flexion has on syndesmotic reduction, and based on our results we would suggest that inclusion of Achilles and other muscle forces would be important in those investigations.…”
Section: Dear Editorsupporting
confidence: 69%
“…It was clearly stated in the discussion on limitations that future studies are needed to investigate the quantitative and qualitative effects of ankle dorsiflexion on Achilles tendon tension and resultant syndesmotic reduction. There is conflicting literature, and conflicting opinion about the appropriate flexion angle for syndesmosis fixation, as summarized nicely in an article by Schon et al 3 We completely agree with the statement that it would be very interesting to determine what effect ankle flexion has on syndesmotic reduction, and based on our results we would suggest that inclusion of Achilles and other muscle forces would be important in those investigations.…”
Section: Dear Editorsupporting
confidence: 69%
“…Imaging studies have shown that single-screw as well as single suture button and divergent suture button fixation all cause a significant volumetric reduction or overcompression of the syndesmosis, suggesting that overconstraint may occur regardless of the fixation technique used. 19,20 A previous biomechanical study demonstrated that syndesmotic injuries can cause inversion instability, and the investigators recommended using additional taping when patients initially return to sports in order to prevent inversion forces. 23 Thus, it might be clinically acceptable to slightly overconstrain tibiofibular motion in response to an inversion torque in plantarflexion in order to protect the anterior talofibular ligament, which is typically injured by this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cadaveric study showed that the SB and SS procedures may overcompress the syndesmosis, particularly with 2 SBs. 26,27 Therefore, regardless of the procedure used, overcompression either by inadvertent pelvic reduction clamp compression or by the fixation method utilized is possible and demands heightened awareness at the time of reduction.…”
Section: Discussionmentioning
confidence: 99%